2015
DOI: 10.1128/iai.00240-15
|View full text |Cite
|
Sign up to set email alerts
|

The CpAL Quorum Sensing System Regulates Production of Hemolysins CPA and PFO To Build Clostridium perfringens Biofilms

Abstract: Mexico bClostridium perfringens strains produce severe diseases, including myonecrosis and enteritis necroticans, in humans and animals. Diseases are mediated by the production of potent toxins that often damage the site of infection, e.g., skin epithelium during myonecrosis. In planktonic cultures, the regulation of important toxins, such as CPA, CPB, and PFO, is controlled by the C. perfringens Agr-like (CpAL) quorum sensing (QS) system. Strains also encode a functional LuxS/AI-2 system. Although C. perfring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 81 publications
1
20
0
Order By: Relevance
“…Alpha-toxin (cpa) was present in the six C. perfringens isolates in our study. Hence, the importance of its existence is consistent with many previous studies as well as Vidal et al (2015) mentioned that alpha-toxin (cpa) may help in the building of C. perfringens biofilms and incorporated into the matrix, where it was seen partially colocalizing with extracted DNA. Moreover, Smedley et al (2004) had stated that C. perfringens is a major cause of enteric diseases due to the production of several toxins.…”
Section: Discussionsupporting
confidence: 90%
“…Alpha-toxin (cpa) was present in the six C. perfringens isolates in our study. Hence, the importance of its existence is consistent with many previous studies as well as Vidal et al (2015) mentioned that alpha-toxin (cpa) may help in the building of C. perfringens biofilms and incorporated into the matrix, where it was seen partially colocalizing with extracted DNA. Moreover, Smedley et al (2004) had stated that C. perfringens is a major cause of enteric diseases due to the production of several toxins.…”
Section: Discussionsupporting
confidence: 90%
“…Here, we have shown that both components of the extracellular matrix are required for the positive effect of biofilm on conjugation, suggesting that these polymers could help stabilize the donor-recipient pair and compensate for the lack of adhesion factors of ICE Bs1 . Other conjugative elements that are not known to encode adhesion factors, such as pCW3 and Tn 916 , are found in the biofilm-forming bacteria Clostridium perfringens and E. faecalis , respectively ( 57 59 ). Lack of adhesion factors in those elements could be compensated for by the ability of their host cells to form biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…Whether the prominent C. perfringens observed layered on the surface of the necrotic but unsloughed mucosa in NE represents a true biofilm rather than bacteria that are tightly adherent to different ligands exposed through the disease process remains to be determined (Charlebois et al, 2015). The Agr-like quorum-sensing system is involved in regulating production of the alpha toxin (CPA) and perfringolysin (PFO) in building biofilms (Vidal et al, 2015).…”
Section: Deeper Mucosal Intestinal Epithelium Colonizationmentioning
confidence: 99%